Cell-Penetrating Pepducin Therapy Targeting PAR1 in Subjects With Coronary Artery Disease - Gurbel, Paul A.; Bliden, Kevin P.; Turner, Susan E.; Tantry, Udaya S.; Gesheff, Martin G.; Barr, Travis P.; Covic, Lidija; Kuliopulos, Athan (Arteriosclerosis, thrombosis, and vascular biology, 2016)
OBJECTIVE—Pepducins are membrane-tethered, cell-penetrating lipopeptides that target the cytoplasmic surface of their cognate receptor. Here, we report the first human use of a protease-activated receptor-1–based pepducin, which is intended as an antiplatelet agent to prevent ischemic complications of percutaneous coronary interventions. APPROACH AND RESULTS—PZ-128 was administered by 1 to 2 hours continuous intravenous infusion (0.01–2 mg/kg) to 31 subjects with coronary artery disease or multiple coronary artery disease risk factors. Safety, antiplatelet efficacy, and pharmacokinetics were assessed at baseline and 0.5, 1, 2, 6, 24 hours, and 7 to 10 days postdosing. The inhibitory effects of PZ-128 on platelet aggregation stimulated by the protease-activated receptor-1 agonist SFLLRN (8 μmol/L) at 30 minutes to 6 hours were dose dependent with 20% to 40% inhibition at 0.3 mg/kg, 40% to 60% at 0.5 mg/kg, and ≥80% to 100% at 1 to 2 mg/kg. The subgroup receiving aspirin in the 0.5 and 1-mg/kg dose cohorts had 65% to 100% inhibition of final aggregation to SFLLRN at 30 minutes to 2 hours and 95% to 100% inhibition by 6 hours. The inhibitory effects of 0.5 mg/kg PZ-128 were reversible with 50% recovery of aggregation to SFLLRN by 24 hours. There were no significant effects of PZ-128 on aggregation induced by AYPGKF, ADP, or collagen, indicating that the observed effects were specific to protease-activated receptor-1. The plasma half-life was 1.3 to 1.8 hours, and PZ-128 was nondetectable in urine. There were no effects on bleeding, coagulation, clinical chemistry, or ECG parameters. CONCLUSIONS—PZ-128 is a promising antiplatelet agent that provides rapid, specific, dose dependent, and reversible inhibition of platelet protease-activated receptor-1 through a novel intracellular mechanism. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierNCT01806077.